EVALUATING THE USEFULNESS OF GAMIFIED ANTI-ANXIETY MOBILE APPLICATION USING HEDONIC-MOTIVATION SYSTEM ADOPTION MODEL (HMSAM) - Nurul Asyikin, Abdullah Abu Bakar (Universiti Malaysia Sarawak (UNIMAS), 2023)
Nowadays, anxiety has been one of the most common mental health issues affecting communities especially university students. A lot of mobile applications invented as interventions for various users to cope with their anxiety symptoms. This project aimed to evaluate the usefulness of a gamified mobile application for anxiety, ‘Rootd’ using Hedonic-Motivation System Adoption Model (HMSAM). In this study, the results were obtained from a survey which involved 30 participants from various universities and programmes. To observe the correlations between each HMSAM constructs, statistical data analysis was conducted including the reliability test using Cronbach’s alpha and validity analysis using confirmatory factor analysis (CFA). The results show that perceived ease of use significantly affects perceived usefulness and perceived usefulness significantly affects behavioural intention to use the mobile application. However, some limitations of the study are identified whereby the study was conducted with a relatively small sample size of 30 respondents. Future study should consider increasing the number of participants in order to improve the reliability of findings. Besides, this project relies on self-reported measurements only for data collection which is through the questionnaire. Utilizing different approaches in data collection such as interview or observations can contribute more to the insight of user’s interaction with the mobile application. Moreover, the study focuses on collecting data at a particular time instead of prolonged period of time. Future works should consider extending the data collection period to gain better insights on usage patterns of the mobile application and its long-term efficacy